2015
DOI: 10.1007/s00248-015-0629-0
|View full text |Cite
|
Sign up to set email alerts
|

A Perspective on the Global Pandemic of Waterborne Disease

Abstract: Waterborne diseases continue to take a heavy toll on the global community, with developing nations, and particularly young children carrying most of the burden of morbidity and mortality. Starting with the historical context, this article explores some of the reasons why this burden continues today, despite our advances in public health over the past century or so. While molecular biology has revolutionized our abilities to define the ecosystems and etiologies of waterborne pathogens, control remains elusive. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 45 publications
0
10
0
Order By: Relevance
“…While the term has gained increased traction in recent years as a means to encourage community empowerment, facilitate capacity building, enable exchange between community members and scientists, and link research directly to policy action, recent review has suggested it also has the potential to substantially improve the rigor, relevance and reach of science (Balazs and Morello-Frosch 2013). Rigorous methodologies applicable to source drinking water monitoring and improvement of quality have yet to be delineated (Ford and Hamner 2015). The human health problems related to the deteriorating surface water quality faced by the communities at Lake Atitlán present a challenging situation in which to critically employ and improve these approaches to benefit lakeside communities and scientific engagement, particularly given the persistent challenges faced by implementation of POU interventions within communities.…”
Section: Community-based Participatory Research (Cbpr)mentioning
confidence: 99%
“…While the term has gained increased traction in recent years as a means to encourage community empowerment, facilitate capacity building, enable exchange between community members and scientists, and link research directly to policy action, recent review has suggested it also has the potential to substantially improve the rigor, relevance and reach of science (Balazs and Morello-Frosch 2013). Rigorous methodologies applicable to source drinking water monitoring and improvement of quality have yet to be delineated (Ford and Hamner 2015). The human health problems related to the deteriorating surface water quality faced by the communities at Lake Atitlán present a challenging situation in which to critically employ and improve these approaches to benefit lakeside communities and scientific engagement, particularly given the persistent challenges faced by implementation of POU interventions within communities.…”
Section: Community-based Participatory Research (Cbpr)mentioning
confidence: 99%
“…The impact of waterborne diseases and sanitation-related infections on mortality and global burden continue to be a major public health issue, especially on the poorest communities (low-income countries) and on vulnerable groups, such as the elderly and children under 5 years old [ 19 ]. In the European Union (EU), the burden of disease is often underestimated, mainly due to the reduced duration of the illness, as not all ill people seek for medical care, and errors in the diagnosis and notification of the cases [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…Water is essential for human life and productivity, yet both water quality and security are increasingly under threat globally [1,2,3]. Unfortunately, while wealthy countries are able to afford effective water treatment, poorer nations are severely hampered by a lack of resources for safe water to protect public health.…”
Section: Introductionmentioning
confidence: 99%